2020
DOI: 10.1038/s41598-020-66895-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporal radiographic changes in COVID-19 patients: relationship to disease severity and viral clearance

Abstract: COVID-19 is "public enemy number one" and has placed an enormous burden on health authorities across the world. Given the wide clinical spectrum of COVID-19, understanding the factors that can predict disease severity will be essential since this will help frontline clinical staff to stratify patients with increased confidence. To investigate the diagnostic value of the temporal radiographic changes, and the relationship to disease severity and viral clearance in COVID-19 patients. In this retrospective cohort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Similarly, in data in the USA (March 31, 2020), chronic respiratory diseases were comorbidities in 8.5% of patients with COVID-19, compared to the GBD estimate of 11.3% for the same disease 5 . There are also several published studies showing the synergistic effect of CLD in worsening the severity of COVID-19 [6][7][8][9][10] . Guan et al reported more than 50% of chronic pulmonary disease for COVID-19 patients who were also admitted to ICU 11 .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Similarly, in data in the USA (March 31, 2020), chronic respiratory diseases were comorbidities in 8.5% of patients with COVID-19, compared to the GBD estimate of 11.3% for the same disease 5 . There are also several published studies showing the synergistic effect of CLD in worsening the severity of COVID-19 [6][7][8][9][10] . Guan et al reported more than 50% of chronic pulmonary disease for COVID-19 patients who were also admitted to ICU 11 .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Similarly, in data in the USA (Mar 31, 2020), chronic respiratory diseases were comorbidities in 8.5% of patients with COVID-19, compare to the GBD estimate of 11.3% for the same disease [5] . Several published studies show the synergistic effect of CLD in worsening the severity of COVID-19 [6][7][8][9][10] . Guan et al reported that more than 50% of chronic pulmonary disease for COVID -19 patients admitted to the ICU [11] .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…The morphological changes in the peripheral lungs of patients with moderate or severe disease [17][18][19][20] create imaging markers in chest radiographs. Chest imaging can play an important role in the clinical management of patients with COVID-19 that have clinical manifestations or worsening respiratory symptoms due to COVID-19 21,22 .…”
Section: Introductionmentioning
confidence: 99%